The Complexity of Semantic Components in Linguistic Era (Journal of the College of Basic Education, 2023)
In Section One, a brief account is made to describe how asemantic theory explains and shows the interpretative ability of speakers.Any lexical item in a given sentence is supplied with more senses, by adictionary, than it can bear. The task of the projection rules is to selectthe most suitable sense of each item in that sentence. The semanticcomponents discussed according to the phonological and semanticrepresentation of sentence which is the basic concern of Section Two, areassociated with a linguistic description of a natural language proposedthe specification of the interconnections between the three components:syntax, phonology and semantics to be of mutual dependency. SectionThree advocates another split from the Standard Theory which is calledGenerative Semantics: a theory developed by Lackoff, McCawley, Rossand others has found its way since 1968 as a strong opponent to theExtended Theory. We also, in Section Four discuss the semanticacceptability in linguistics through drawing a distinction betweengrammaticality (a property belonging to a competence) and acceptability(a property identical in performance).